PENDAMPINGAN PENGGUNAAN APLIKASI AKUNTANSI DAN PEMASARAN BERBASIS ANDROID (e LEATHERSGOOD.ID) PADA KELOMPOK UMKM TAS GOLF DAN KERAJINAN KULIT DESA KALITENGAH SIDOARJO - Duwi Rahayu; Hamzah Setiawan; Alshaf Pebrianggara (Universitas Mataram, 2023)
The MSME group of golf bags and leather handicrafts of Kalit tengah Sidoarjo village is one of the groups affected by covid 19. The MSME group has difficulties in terms of accounting and marketing records which have an impact on the development of MSMEs. The MSME group sometimes finds it difficult in terms of android-based marketing and the thought